리스크 기반의 위성 제품보증 및 테일러링 분석 - 송수아(Sua Song); 장영근(Young-Keun Chang) (항공우주시스템공학회지, 2018)
Space agencies such as NASA, ESA, and the US military provide guidelines and standards for PA(product assurance) requirements and plans. In recent years, major satellite manufacturers around the world have been mitigating PA requirements and processes by tailoring. PA tailoring has been implemented to improve the cost and schedule efficiency. PA tailoring can be accomplished based on various factors such as mission, classification of mission risk, complexity, development cost, life cycle, etc. In this study, PA tasks according to the mission risk classification proposed by NASA are investigated, and the tailoring method is suggested for the optimization of the development cost and schedule. In particular, the classification of mission risk for the satellites under development or operation in Korea is performed, and PA characteristics in accordance with mission risk are analyzed. 미 항공우주국(NASA), 유럽우주기구(ESA) 등의 우주기관 및 미국 군에서는 제품보증 수행에 대한 요구조건 및 계획 등에 대한 가이드라인 또는 표준서를 제시하고 있다. 최근 들어, 세계의 주요 위성제작사는 테일러링(tailoring)을 통해 과도한 제품보증 요구조건 및 프로세스를 완화하고 있다. 비용 및 일정의 효율성을 증진시키기 위한 테일러링을 수행한다는 의미이다. 제품보증 테일러링은 임무, 임무 리스크의 유형, 복잡도, 개발비용 및 수명주기 등의 다양한 인자를 기준으로 수행될 수 있다. 본 연구에서는 NASA에서 제안된 임무 리스크(mission risk) 분류에 따른 제품보증 업무를 조사하고, 개발비용 및 일정의 최적화를 위한 테일러링 방안을 제시한다. 특히, 국내에서 개발하여 운용 중이거나 개발 중인 위성에 대한 임무 리스크 유형을 정의하고 이들에 대한 제품보증 특성을 비교 분석한다.